Pengembangan Sistem Akuaponik : Sinergi Hidroponik dan Kolam untuk Ketahanan Pangan dan Ekonomi Lokal pada Desa Sukolilo Kabupaten Malang - Okta Bryan Yudi Pratama; Muhammad Virsa Irawan; Ardhan Ardiansyah Kawakibi (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
Food security and community economic empowerment are major challenges in many rural areas, including Sukolilo Village. This research aims to develop and analyze the effectiveness of an aquaponic system, a combination of hydroponics and fish farming, as an innovative sustainable solution. The methods used include observation, experimentation, and interviews with the local community. The results showed that the aquaponic system is able to increase agricultural productivity with better water use efficiency and provide economic benefits through crop diversification, namely vegetables and fish. In addition, the system is proven to be environmentally friendly as it utilizes organic waste from fish as plant nutrients, reduces the use of chemical fertilizers, and optimizes local resources. The implementation of the aquaponic system in Sukolilo Village not only improves food security but also opens up new business opportunities for the community, thus contributing to the improvement of local economic welfare. It is hoped that this model can be replicated in other areas as part of a sustainable agriculture-based economic development strategy.